Creep Grazing for Suckling Calves - A Pasture Management Practice - Yoana C. Newman; Doug E. Mayo; Joao Vendramini; Carrol G. Chambliss (EDIS)
The concept of creep grazing is based on the fact that the nutritional requirements of suckling calves are much higher than those of cows. Calves creep grazing on high quality forage that provides high intake of digestible energy and protein make extra growth while the cows are grazing lower quality pasture. Learn more in this revised 4-page fact sheet written by Y.C. Newman, D.E. Mayo, J. Vendramini, and C.G. Chambliss and published by the UF Department of Agronomy, March 2011.